2012
DOI: 10.1242/jeb.070300
|View full text |Cite
|
Sign up to set email alerts
|

A flavonol present in cocoa [(−)epicatechin] enhances snail memory

Abstract: SUMMARYDietary consumption of flavonoids (plant phytochemicals) may improve memory and neuro-cognitive performance, though the mechanism is poorly understood. Previous work has assessed cognitive effects in vertebrates; here we assess the suitability of Lymnaea stagnalis as an invertebrate model to elucidate the effects of flavonoids on cognition. (-)Epicatechin (epi) is a flavonoid present in cocoa, green tea and red wine. We studied its effects on basic snail behaviours (aerial respiration and locomotion), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 74 publications
(105 reference statements)
4
46
0
Order By: Relevance
“…Using this procedure GT was shown to enhance or to reverse a blockade of LTM formation [1315]. Here we found (Figure 2) that training in the 1:14 BT blocked LTM formation.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Using this procedure GT was shown to enhance or to reverse a blockade of LTM formation [1315]. Here we found (Figure 2) that training in the 1:14 BT blocked LTM formation.…”
mentioning
confidence: 58%
“…a 24 h memory) two 0.5h training sessions separated by a 1h interval are necessary. The W- strain has been used extensively in our laboratory and is the same strain used in the previous experiments testing the effects of Epi and Epi-containing foods on cognition in Lymnaea [2,1316]. In this strain a single 0.5h TS does not result in LTM formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exposing snails to epicatechin significantly enhanced the ability of snails to form LTM (Fruson et al, 2012). The epicatechinenhanced LTM formed faster, persisted longer, and was more resistant to extinction.…”
Section: Introductionmentioning
confidence: 97%
“…A comprehensive summary of which ecologically relevant stressors significantly alter LTM formation can be found in two recent reviews (Lukowiak et al, 2014). It has also been shown that a flavonoid, epicatechin, found in dark chocolate, green tea and red wine (Kühnau, 1976;Matsuoka et al, 1995;Galliet al, 2002;Youdim et al, 2002) enhances LTM formation in Lymnaea (Fruson et al, 2012). However, the enhancement brought about by epicatechin occurs via a different mechanism than that brought about by predator detection (Il-Han et al, 2010;Fruson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%